2005
DOI: 10.1080/00420980500279828
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Budgeting in Porto Alegre: Social Innovation and the Dialectical Relationship of State and Civil Society

Abstract: This article focuses on the identification and role of social innovation in urban development. The aim is to further the understanding of the contradictory relationship between state and civil society, using a thorough analysis of the process of participatory budgeting in Porto Alegre, the capital city of Rio Grande do Sul-the most southern state of Brazil. The first section spells out four different concepts of the relationship between state and civil society and their implications for social innovation. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
22

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(104 citation statements)
references
References 16 publications
1
80
0
22
Order By: Relevance
“…In this meaning these movements themselves are seen as a SI, irrespective of their outputs. The second meaning is narrower, and refers to the strategies that individuals and organisations that are part of these movements devise to develop, strengthen or reinvigorate their cause (Novy and Leubolt, 2005;Papakostas, 2011). This meaning is closer to what we would call targeted radical SI, which will be discussed in greater detail in subsequent paragraphs.…”
Section: The Meaning(s) Of Social Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this meaning these movements themselves are seen as a SI, irrespective of their outputs. The second meaning is narrower, and refers to the strategies that individuals and organisations that are part of these movements devise to develop, strengthen or reinvigorate their cause (Novy and Leubolt, 2005;Papakostas, 2011). This meaning is closer to what we would call targeted radical SI, which will be discussed in greater detail in subsequent paragraphs.…”
Section: The Meaning(s) Of Social Innovationmentioning
confidence: 99%
“…We argue instead that this lack of rigour limits the potential of this concept, as a tool for both research and action. Based on our literature review, we observed that articles using the term SI often shift seamlessly between definitions of what SI is and what it should be (Borzaga and Bodini, 2014;Cajaiba-Santana, 2014;Grimm et al, 2013;Mieg and To¨ pfer, 2013;Novy and Leubolt, 2005;Pol and Ville, 2009). This use of the term occasionally leaves the reader unaware of what has been observed in practice and what the agents on the field, or the author, would like to have seen happen as a result of their own values.…”
Section: The Meaning(s) Of Social Innovationmentioning
confidence: 99%
“…Participatory Budgeting is therefore also labelled "citizenship school" [12]. Through taking part in public discussions, individual participants learn to relate their personal needs to the public interest, in addition, they learn to appreciate the needs of others [27]. The citizenship school is open to all.…”
Section: Pbs Transformative Potentialmentioning
confidence: 99%
“…Porto Alegre (Brazil), which implemented the first participatory budget in 1989 to fight corruption in administrations [35,36], is one of the most studied cases in the field of participatory budgeting (see e. g. [4,15,22]). Participatory budgeting in Porto Alegre is running throughout the year and composed of four main phases [15, p. 54]: (1) prioritizing topics through citizenship, (2) elaborating the budget proposal, (3) enacting the budget in city council and (4) elaborating, implementation and control of the investment plan.…”
Section: Participatory Budgetingmentioning
confidence: 99%